Agricultural land availability and farmer’s income in Java Island, Indonesia, 1990–2018 - Prasada, Imade Yoga (Hungarian Central Statistical Office, 2022)
Java, an island in Indonesia, plays an essentialrole as the centre of food crop production.However, over the last few decades, theconversion of agricultural land on this islandhas increased. The pressure on the availabilit yof agricultural land has increased, and theproblems regarding farmers’ income have no tbeen appropriately resolved. This research wasconducted to determine the relationshipbetween the availability of agricultural land andfarmers’ income on Java Island using structuralequations. The panel data used in this researchconsist of annual time-series data from 1990–2018 and cross-section data of all provinces inJava. Furthermore, the data were analyse dusing a three-stage least-squares model. Theresults prove that agricultural land availabilityand the level of farmers' incomesimultaneously positively affect each other.Therefore, to maintain the performance o fJava Island as the primary producer of foo dcrops in Indonesia, the availability ofagricultural land and the level of farmers'income are the main focus areas for improvement.